(untitled) (International Association of Biologicals and Computational Digest, 2022)
This paper quantifies the present status of Mangrove covers in the estuarine region of Purna River, Gujarat. Mangroves health assessment and change detection is modelled after contemplation of important health indicators such as canopy cover, drainage density, erosion and accretion, reclamation activities, and natural regeneration. The weightage of each parameter is given based on its relative importance in mangrove’s health. The entire study area is overlaid with a uniform grid of 1 × 1 hectare, where each parameter is calculated and mapped using multispectral LISS-IV satellite imageries of different time frames between 2008 and 2018 along with the in-situ field measurements. Our analysis showed that the mangrove area of approximately 0.094 sq.km has been degraded from 2008 to 2018 and about 0.126 sq.km has undergone degradation. Whereas the mangroves present on island patches are showing an improvement especially observed along the creek. The area under the pristine health condition of mangroves has been reduced to 0.336 sq. km. One of the major reasons was the construction of aquaculture ponds, which was increased from 2.937 sq.km in 2014 to 7.659 sq.km in 2018. The secondary factor is the wave activity near the mouth of the estuary, which is causing severe erosion along the coast and thereby affecting the mangrove trees.